In silico genomic analysis of the potential probiotic Lactiplantibacillus pentosus CF2-10N reveals promising beneficial effects with health promoting properties - Abriouel, Hikmate; Manetsberger, Julia; Caballero Gómez, Natacha; Benomar, Nabil (Frontiers in Microbiology, 2022)
Lactiplantibacillus pentosus CF2-10 N, isolated from brines of naturally fermented Aloreña green table olives, exhibited high probiotic potential. High throughput sequencing and annotation of genome sequences underline the potential of L. pentosus CF2-10 N as excellent probiotic candidate of vegetable origin. In a previous study we could show the probiotic potential of CF2-10 N in vitro, while in this study in silico analysis of its genome revealed new insights into its safety and functionality. Our findings highlight the microorganism’s ecological flexibility and adaptability to a broad range of environmental niches, food matrices and the gastrointestinal tract. These features are shared by both phylogenetically very close L. pentosus strains (CF2-10 N and MP-10) isolated from the same ecological niche with respect to their genome size (≅ 3.6 Mbp), the presence of plasmids (4–5) and several other properties. Nonetheless, additional and unique features are reported in the present study for L. pentosus CF2-10 N. Notably, the safety of L. pentosus CF2-10 N was shown by the absence of virulence determinants and the determination of acquired antibiotic resistance genes, i.e., resistome, which is mostly represented by efflux-pump resistance genes responsible for the intrinsic resistance. On the other hand, defense mechanisms of L. pentosus CF2-10 N include eight prophage regions and a CRISPR/cas system (CRISPR-I and CRISPR-II) as acquired immune system against mobile elements. Finally, the probiotic potential of this strain was further demonstrated by the presence of genes coding for proteins involved in adhesion, exopolysaccharide biosynthesis, tolerance to low pH and bile salts, immunomodulation, and vitamin and enzyme production. Taken together these results, we propose the use of L. pentosus CF2-10 N as a potential and promising probiotic candidate able to colonize several niches and adapt to different lifestyles. The strain can provide attractive functional and probiotic features necessary for its application as starter culture and probiotic.